Quality Assurance in The Surgical Ward of Hospital X in Bandung During the Covid- 19 Pandemic - Richa Noprianty; Fikri Mourly Wahyudi; Wahyu Wahdana; Tata Juarta (International Journal of Quantitative Research and Modeling, 2023)
Health services are organised to meet the needs and demands of the community. If fulfilled, it will lead to client satisfaction. Hospital X in Bandung had a BOR of 91,67% in 2021 during the Covid-19 era. This BOR surpasses the WHO standard. Thus the quality of service needs to be assessed. The research was conducted to get an overview of the level of patient satisfaction with inpatient services at the surgical ward of Hospital X in Bandung. The study was conducted using an exploratory, descriptive approach to obtain an objective picture. Data was collected by filling out questionnaires to patients and families of 90 people. Samples were selected purposively with inclusion criteria: respondents must be treated for at least three days. The instrument was prepared concerning the “Hospital Service Quality Assurance” guidelines. The results showed that 53.4% of respondents stated that the quality of inpatient services at Hospital X in Bandung was in an outstanding category starting from the aspect of registration, nurse services, medical services, food and menus, comfort and cleanliness, medical facilities to administration, and finance. Health services carried out by hospitals are constantly changing along with the development of science and technology, and hospitals are preparing for hospital accreditation. It is recommended that hospitals continue to improve the quality of their services so that patient satisfaction with the services received can be maintained.